KLİNİKTE EKİP ANLAYIŞININ ÖNEMİ VE ÖĞRENCİYE KAZANDIRILMASI - ALTUNTAŞ ÇALIM, Gülşen; ELMAS, Semra (Göbeklitepe Medical Science Journal, 2021)
One of the most important factors in the provision of qualified health services is the presence of health professionals and effective communication, cooperation and team understanding with each other. This situation shows that health services and delivery is an interdisciplinary system based on teamwork. In various studies, it has been observed that effective teamwork increases patient safety, quality of care and team members' motivation, as well as decreases, cost, hospital stay, and medical errors, and decreases mortality rates. Indeed, many of the incidents that violate patient safety in health services are attributed to the lack of effective communication and teamwork. It is also observed that it is not possible for the team members to perform the activities in the process along with the knowledge and skills of the health service. It is also important to teach such an important concept to the students who will take part in the provision of health services during their education. In this sense, the basic concepts of teamwork were explained in our study, and it was emphasized why teamwork is important in clinical practice for students.